Ion‐Conducting, Electron‐Blocking Layer for High‐Performance Solid Electrolytes. Issue 8 (5th May 2021) - Hitz, Emily M.; Xie, Hua; Lin, Yi; Connell, John W.; Rubloff, Gary W.; Lin, Chuan-Fu; Hu, Liangbing
Abstract : Lithium metal batteries bring greater promise for energy density, often relying on solid‐state electrolytes to meet critical benchmarks. However, Li dendrite formation is a prevailing problem that limits the cycle life and Coulombic efficiency of solid‐state Li metal batteries. For the first time, a thin (<100 nm) layer of electronically insulating, ionically conducting lithium phosphorus oxynitride (LiPON) is applied using atomic layer deposition between a Li anode and garnet Li7 La3 Zr2 O12 (LLZO). The performance of a conformal LiPON layer as an electron barrier in symmetric Li‐LLZO cells is observed through potential step chronoamperometry, galvanostatic cycling, electron microscopy, and various spectroscopic techniques. The LiPON‐coated LLZO achieves 100 times lower electronic conductance than LLZO alone. Cycling carried out at 0.1 mA cm −2 for 100 cycles demonstrates that suppression of electron pathways into the bulk solid electrolyte improves the cycle life of a lithium metal cell. These findings suggest an electronic conductivity effect in solid‐state electrolytes. A strategy is demonstrated to design thin‐film (LiPON)‐modulated bulk solid‐state electrolytes (LLZO) capable of maintaining high ionic conductivity and electrochemical stability while reducing the effective electronic conductivity, which results in significantly decreased dendrite formation, improved cycle life, and greater interfacial integrity between the electrolyte and a Li anode. Abstract : A strategy is demonstrated to design electron‐blocking layer, ion‐conducting thin‐film (LiPON)‐modulated bulk solid‐state electrolytes (LLZO), that is capable of maintaining high ionic conductivity and electrochemical stability while reducing the effective electronic conductivity, which results in significantly decreased dendrite formation, improved cycle life, and greater interfacial integrity between the electrolyte and a Li anode.